THE INFLUENCE OF THE RANUB LAMPUAN DANCE IN THE IMPLEMENTATION OF ADAB TO GLORIZE GUESTS - Iqbal, Muhammad (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2024)
The aim of this research is to find out the process of extracurricular dance activities and the values ​​of character education at SD Negeri 13 Banda Sakti, Lhokseumawe City. This type of research is field research that uses a qualitative approach and is located at SD Negeri 13 Banda Sakti, Lhokseumawe City, Electric Road, Banda Sakti, Lhokseumawe City. Research methods include observation methods, interview methods, documentation methods. The data validity checking technique used is data triangulation. The results of the research show that the dance extracurricular at SD Negeri 13 Banda Sakti, Lhokseumawe City was held based on the request of the parents and students until 2023. The purpose of the dance extracurricular is as a forum for developing students' talents and interests in the field of dance. The dance extracurricular activity process is carried out once a week and is attended by 7 students from class V who are formed into 1 group. The extracurricular dance material is the Ranub Lampuan dance. The sequence of events for each opening and closing practice. The tools used in the Ranub Lampuan dance extracurricular are loudspeakers, flash disks and laptops. Furthermore, the character education values ​​found in extracurricular activities include religious dance, tolerance, discipline, hard work, curiosity, love of the country, respect for achievement, friendship or communicativeness, responsibility, and caring for the environment. Based on the research results, it can be concluded that the implementation of dance extracurricular activities can shape the manners of students who are members of the Ranub Lampuan dance extracurricular at SD Negeri 13 Banda Sakti, Lhokseumawe City.